Predicted shortage of vascular surgeons in the United Kingdom: A matter for debate?. Issue 5 (October 2016) - Harkin, D.W.; Beard, J.D.; Shearman, C.P.; Wyatt, M.G.
Abstract: Background: Vascular surgery became a new independent surgical specialty in the United Kingdom (UK) in 2013. In this matter for debate we discuss the question, is there a "shortage of vascular surgeons in the United Kingdom?" Materials and methods: We used data derived from the "Vascular Surgery United Kingdom Workforce Survey 2014", NHS Employers Electronic Staff Records (ESR), and the National Vascular Registry (NVR) surgeon-level public report to estimate current and predict future workforce requirements. Results: We estimate there are approximately 458 Consultant Vascular Surgeons for the current UK population of 63 million, or 1 per 137, 000 population. In several UK Regions there are a large number of relatively small teams (3 or less) of vascular surgeons working in separate NHS Trusts in close geographical proximity. In developed countries, both the number and complexity of vascular surgery procedures (open and endovascular) per capita population is increasing, and concerns have been raised that demand cannot be met without a significant expansion in numbers of vascular surgeons. Additional workforce demand arises from the impact of population growth and changes in surgical work-patterns with respect to gender, working-life-balance and 7-day services. Conclusions: We predict a future shortage of Consultant Vascular Surgeons in the UK and recommend an increase in training numbers and an expansion in the UK Consultant Vascular Surgeon workforce to accommodate population growth, facilitate changes in work-patterns and to create safe sustainable services.